Detection of absolute rotation using superfluid 4He - Schwab, K.; Bruckner, N.; Packard, R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
We have developed the superfluid analog of the superconducting rf SQUID. Such a device is a quantum mechanically based, absolute gyroscope and has been used to sense the rotation of the Earth. Our device is fabricated using silicon processing techniques and forms a planer sensing loop of superfluid helium which couples to the applied rotation. A much more sensitive superfluid gyroscope based on the principals demonstrated with this device, might ultimately be used to detect the precession of our local inertial frame with respect to the fixed stars by the gravitomagnetic field of the rotating Earth. We compare the superfluid gyroscope against two other experiments aimed at detecting this general relativistic effect.